2007
DOI: 10.1007/s00508-007-0895-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation der Behandlungsergebnisse einer psychiatrischen Aufnahmestation

Abstract: Using the presented evaluation system therapy outcome and quality of therapy are easy to assess. The results of the quality assessment can be used in further therapeutic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The SCL-90-R was first described by Derogatis (31) and includes 90 items which define the global extent of psychological symptoms on self-rater basis. However, it has been found that 90 items might be too lengthy and time-consuming, especially for (severely) mentally ill patients (26,32,33). Therefore, we chose the SCL-K-9 instrument.…”
Section: Symptom Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…The SCL-90-R was first described by Derogatis (31) and includes 90 items which define the global extent of psychological symptoms on self-rater basis. However, it has been found that 90 items might be too lengthy and time-consuming, especially for (severely) mentally ill patients (26,32,33). Therefore, we chose the SCL-K-9 instrument.…”
Section: Symptom Severitymentioning
confidence: 99%
“…A high sum score indicates high and a low sum score low symptom severity. More information on the instrument and scoring can be obtained elsewhere (26,37).…”
Section: Symptom Severitymentioning
confidence: 99%